Clinical anastomosis leakage and determinant factors among patients who underwent intestinal anastomosis in two Ethiopian tertiary hospitals - Yilkal Teshome Numaro; Molla Asnake Kebede; Shimelis Nigussie G. Mariam; Nelbyou Seyoum Abebe; Bizuayehu Tassew Gossaye; Sebsibe Dingetu Shenga; Hezron Adinew Addi; Melkamu Mitikie Melak; Turi Abateka Abadiga; Henok Birhanu Kassa (BMC Gastroenterology)
Abstract Introduction Intestinal anastomosis is a common surgical procedure, but anastomotic leaks remain significant postoperative complications, causing morbidity, prolonged hospital stays, and readmissions. This study aimed to identify the rate, determinant factors, and outcomes associated with anastomotic leakage for patients undergo gastrointestinal anastomoses in two major hospitals in Addis Ababa, Ethiopia. Method A retrospective cross-sectional study was conducted. 206 patients who underwent bowel anastomosis between 2016 and 2019 GC. To assess determinant factors first bivariate analysis was done for all independent variables and for variables with p-value < 0.2 multiple logistic regression was performed to identify independent predictors of anastomotic leakage. Odds ratios were computed; and a p-value < 0.05 was considered statistically significant and Hosmer–Lemeshow goodness-of-fit test was run to ascertain the fitness of the model. Results The clinical anastomotic leakage (AL) rate in this study was 8.3% (95%CI; 5.4–9.1). A total of 14 patients died in the study sites making the mortality rate was 6.8%. The presence of gangrenous bowel at the time of surgery was a strong independent predictor of AL (AOR 4.88; 95% CI: 1.62–14.69; p < 0.001). Intraoperative blood loss greater than 500 mL was also significantly associated with an increased risk of leakage (AOR 3.13; 95% CI: 1.07–9.17; p = 0.029). Moreover, patients who developed anastomotic leakage had a higher risk of mortality (AOR 5.495; 95% CI: 1.517–20.00; p = 0.004). AL was also associated with prolonged hospital stay beyond 20 days (AOR 5.49; 95% CI: 1.99–7.12; p = 0.000). 3.13; (1.07–9.17). Conclusion In this study, anastomotic leakage was found to be higher than expected. Bowel viability and the amount of Blood loss was significant predictors of clinical anastomotic leakage. Additionally, the presence of anastomotic leakage was associated with increased mortality and prolonged hospitalization.